Possibility of venoarterial extracorporeal membranous oxygenator being a bridging therapy for hemodynamic deterioration of pulmonary tumor thrombotic microangiopathy prior to initiating chemotherapy: A case report. Issue 37 (September 2018) - Iwashita, Yoshiaki; Hiramoto, Takuya; Suzuki, Kei; Hashizume, Ryotaro; Maruyama, Kazuo; Imai, Hiroshi
Abstract: Rationale: Pulmonary tumor thrombotic microangiopathy (PTTM) is a rare but lethal complication of carcinoma, defined as non-occlusive pulmonary tumor embolism complicated by fibrocellular intimal proliferation of the small pulmonary arteries, with eventual occlusion of the pulmonary arteries. Hemodynamic deterioration caused by this condition leads to high mortality. Patient concerns: A 46-year-old woman who had undergone radiation therapy for anaplastic oligoastrocytoma and who was taking temozolomide presented with cough and palpitations. Diagnoses: A 12-lead electrocardiogram showed sinus tachycardia and SIQIII TIII, with negative T in V1–3. Ultrasound cardiography showed a distended right ventricle. Enhanced chest computed tomography showed no significant thrombus in the major pulmonary artery. The patient's condition deteriorated the next morning, with her blood pressure decreasing to 40 mmHg and her SpO2 unmeasurable. She suffered cardiac arrest. Interventions: We initiated venoarterial extracorporeal membranous oxygenation (VA-ECMO) and her blood pressure increased to 80 mmHg. Her hemodynamic status stabilized and she was weaned off VA-ECMO on intensive care unit (ICU) day 3. Outcomes: Gastroesophageal endoscopy on ICU day 4 revealed gastric cancer (Borrman type IV), and she arrested again and died on ICU day 5. Autopsy confirmed gastric cancer and PTTM. Lessons: VA-ECMO rapidly stabilized the hemodynamic status of this patient with PTTM, and may thus be a possible bridging therapy for deterioration of PTTM prior to initiating imatinib.